2016
DOI: 10.3389/fnins.2016.00394
|View full text |Cite
|
Sign up to set email alerts
|

Using Individualized Brain Network for Analyzing Structural Covariance of the Cerebral Cortex in Alzheimer's Patients

Abstract: Cortical thinning patterns in Alzheimer's disease (AD) have been widely reported through conventional regional analysis. In addition, the coordinated variance of cortical thickness in different brain regions has been investigated both at the individual and group network levels. In this study, we aim to investigate network architectural characteristics of a structural covariance network (SCN) in AD, and further to show that the structural covariance connectivity becomes disorganized across the brain regions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 69 publications
0
38
0
Order By: Relevance
“…Random networks are computed having a random topology but sharing the size, density and binary degree distribution of the original network (Maslov and Sneppen, 2002). Cluster coefficient (Kim et al, 2016; Zhang et al, 2016) is a measure of segregation and is the average value of the cluster coefficients of each node C i computed as follows (Rubinov and Sporns, 2010): leftCi=tikifalse(ki-1false) where k i is the degree of the node, and t i is the number of triangles around the node. Since the ( i, j ) element in the n 'th power of an adjacency matrix counts the number of path of length n starting at i and ending at j , the number of triangles of node i coincides with the value of the i -th diagonal element of the 3rd power of the adjacency matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Random networks are computed having a random topology but sharing the size, density and binary degree distribution of the original network (Maslov and Sneppen, 2002). Cluster coefficient (Kim et al, 2016; Zhang et al, 2016) is a measure of segregation and is the average value of the cluster coefficients of each node C i computed as follows (Rubinov and Sporns, 2010): leftCi=tikifalse(ki-1false) where k i is the degree of the node, and t i is the number of triangles around the node. Since the ( i, j ) element in the n 'th power of an adjacency matrix counts the number of path of length n starting at i and ending at j , the number of triangles of node i coincides with the value of the i -th diagonal element of the 3rd power of the adjacency matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The potential role of disruption to the SCN to understanding functional outcomes has been explored within a graph theoretic framework in relation to a range of conditions. These include broad psychiatric diagnoses such as bulimia, depression and schizophrenia (Chen et al, 2017;Mak, Colloby, Thomas, & O'Brien, 2016;Palaniyappan, Park, Balain, Dangi, & Liddle, 2015;Tijms et al, 2015;Westwater, Seidlitz, Diederen, Fischer, & Thompson, 2017), neurodegenerative disorders, such as Alzheimer's disease (AD) and multiple sclerosis (Kim et al, 2016;Pereira et al, 2015;Pereira et al, 2016;Raamana, Weiner, Wang, Beg, & Alzheimer's Disease Neuroimaging, 2015;Tewarie et al, 2014), epilepsies (Garcia-Ramos et al, 2017;Sone et al, 2016;Yasuda et al, 2015) and autism spectrum disorders (Balardin et al, 2015). In all of these studies, the methodology requires multiple participants to sample enough cortical measurements to generate a correlation between all possible regional pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Existing methodological approaches have attempted to investigate these structural relationships between regions at the individual-patient level (i.e. (Kim et al, 2016;Kong et al, 2015;Kong et al, 2014;Tijms, Series, Willshaw, & Lawrie, 2012;Yu et al, 2018)). The majority of these methodologies have two major limitations; they either divide ROIs into sub regions that do not respect the underlying structure and convolutions of the cortex (Tijms et al, 2012), or the edge weights are defined as the simple subtraction of the feature in region A minus region B, rather than covariance.…”
Section: Introductionmentioning
confidence: 99%
“…Network-level analysis of cortical thickness and gray matter features demonstrated its potential to provide novel insights or improve predictive power (Raamana et al 2015), and is gaining in popularity (Evans 2013;Wen, He, and Sachdev 2011;Reid and Evans 2013;Jason P. Lerch et al 2006). Thickness network features offer complementary information compared to the underlying fiber density (Gong et al 2012), are shown to be disrupted in AD (Kim et al 2016) and have been shown to have potential for early prognosis of AD (Raamana et al 2015;Wee et al 2012;Dai et al 2012;Kim et al 2016), as well as for subtype discrimination (Raamana, Wen, et al 2014), outperforming the non-network raw-thickness features.…”
Section: Introductionmentioning
confidence: 99%
“…Network analysis studies in cortical thickness range from 1. group-wise studies building networks based on group-wise covariance/correlation in cortical thickness (Evans 2013;He and Chen 2007;Jason P. Lerch et al 2006), which may be used to characterize the properties of these networks (such as small-worldness) as well as provide useful insight into network-level changes between two diagnostic groups e.g. healthy controls (CN) and Alzheimer's disease (AD), 2. studies building individual subject-wise graphs based on within-subject ROI-wise (pairwise) similarity metrics (Raamana et al 2015;Tijms et al 2012;Wee et al 2012;Dai et al 2012;Kim et al 2016) to enable predictive modeling. These studies resulted in disease-related insights into network-level imaging biomarkers and improved accuracy for the early prognosis of AD.…”
Section: Introductionmentioning
confidence: 99%